Respuesta :

corm

Step-by-step explanation:

[tex]x + 2y = 4[/tex]

[tex]2x - y = 3[/tex]

To solve this system of equation, let's multiply the second equation by two so both equations have a [tex]2y[/tex]:

[tex]x + 2y = 4[/tex]

[tex]4x - 2y = 6[/tex]

Next, let's add the two equations together to remove the [tex]y[/tex] and solve for [tex]x[/tex]:

[tex](x + 2y) + (4x - 2y) = 4 + 6[/tex]

[tex]5x = 10[/tex]

[tex]x = 2[/tex]

Now that we have the value of [tex]x[/tex], we can plug it into either of the equations to solve for [tex]y[/tex]:

[tex]x + 2y = 4[/tex]

[tex](2) + 2y = 4[/tex]

[tex]2y = 2[/tex]

[tex]y = 1[/tex]

or

[tex]2x - y = 3[/tex]

[tex]2(2) - y = 3[/tex]

[tex]4 - y = 3[/tex]

[tex]y = 1[/tex]

Therefore, the solution to this system of equations is [tex](2, 1)[/tex].

The solution of the given system of equation is x = 2 and y = 1

Step-by-step explanation:

Given,

x+2y = 4 -------eq 1

2x -y = 3 ------- eq 2

To find the value of x and y

Putting y = 2x-3 from eq 2 in eq 1 we get,

x+2(2x-3) = 4

or, x+4x-6 = 4

or, 5x = 10

or, x = 2

Again,

From eq 2 we get,

y = 2×2-3 = 1

Hence,

x = 2 and y = 1

Checking:

Putting the values of x=2 and y=1 in eq 1 and eq 2 we get,

2 + 2×1 = 4 and

2×2-1 = 3

ACCESS MORE
EDU ACCESS